MORPHOMETRIC ANALYSIS OF THE STRUCTURAL COMPONENTS OF THE DUODENAL WALL IN SIMULATED PANCREATITIS - Shuturma, O.Ya.; Nebesna, Z.M.; Ohinska, N.V.; Zarichna, O.Y.; Lyebyedyeva, T.A. (World of Medicine and Biology, 2022)
The paper presents the data of the morphometric study of the duodenal wall in cryogenic pancreatitis. It has been established that the degree of morphometric changes correlated with the duration of the simulated pathological process. An increase in the thickness of the mucous membrane, the height and thickness of the villi, the thickness of the lamina propria of the mucous membrane and the submucous layer has been noted. It was associated with edema and the inflammatory process in the investigated organ. There was also a tendency to increase in the width and depth of crypts, the height of columnar epitheliocytes in the middle part of the villi, which indicated pronounced hypertrophic changes.